SUPERVISION IN SOCIAL WORK (PANGEEA, 2025)
Supervision in Social Work has an important and priority role in solving problems, which may arise in complex cases, to ensure the quality and strengthen the skills of the social worker. Supervision by professionals is very important if productive social assistance is desired. Effective supervision helps both front-line social workers and case managers to work to the standards imposed by the profession.
Keywords: supervision; social work; profession